2020
DOI: 10.3389/fmicb.2020.560482
|View full text |Cite
|
Sign up to set email alerts
|

Residues 315 and 369 in HN Protein Contribute to the Thermostability of Newcastle Disease Virus

Abstract: Thermostable Newcastle disease virus (NDV) vaccines have been widely used in areas where a "cold-chain" is not reliable. However, the molecular mechanism of NDV thermostability remains poorly understood. In this work, we constructed chimeric viruses by exchanging viral fusion (F) and/or hemagglutinin-neuraminidase (HN) genes between the heat-resistant strain HR09 and thermolabile strain La Sota utilizing a reverse genetic system. The results showed that only chimeras with HN derived from the thermostable virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…2, the results demonstrated mutations S315P, I369V, and V369A among the VII.1.1 isolates. These results are consistent with the recent study [23], which revealed that residues 315, 329, and 369, especially mutations S315P and I369V, could signi cantly enhance the viral thermostability, HA, and NA activities.…”
Section: Discussionsupporting
confidence: 93%
“…2, the results demonstrated mutations S315P, I369V, and V369A among the VII.1.1 isolates. These results are consistent with the recent study [23], which revealed that residues 315, 329, and 369, especially mutations S315P and I369V, could signi cantly enhance the viral thermostability, HA, and NA activities.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the intensive unplanned vaccination in Egypt, selection/vaccination pressure could explain the occurrence of such aa substitutions in the epitopes of Egyptian NDV HN overtime, which in turn may affect, to different levels, the vaccine efficacy, induced immunity, and virus shedding in birds as a result of antigenic variability (108). HN protein is a determinant viral factor for thermostability, as mutant NDV viruses (S315P and I369V) were more thermostable and possessed more HA titers and NA fusion activity (109).…”
Section: Deduced Amino Acid Analysismentioning
confidence: 99%
“…To achieve this goal, a thermostable NDV strain is necessary. Previously, a thermostable NDV HR09 strain, which could stay infectious for more than 100 min under 56 °C, was attenuated using a reverse genetic system in our lab [ 15 , 16 , 41 ]. Compared with the widely used La Sota strain, the attenuated rAHR09 strain could efficiently reduce the NDV virus shedding and provide full protection against the challenge of NDV [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, one thermostable NDV was isolated in our lab, designated HR09, which could remain infectious for more than 1 hour under 56 °C treatment [ 15 ]. Through exchanging the proteins of thermostable HR09 and the La Sota strain, it was found that the residues 315 and 369 in the HN protein were responsible for the thermostability of HR09 [ 16 ]. The thermostable HR09 strain, which belongs to genotype VIII, is a mesogenic NDV strain.…”
Section: Introductionmentioning
confidence: 99%